Everlasting land, student center / Syamil Rifqy Roslan ... [et al.] - Roslan, Syamil Rifqy; Mat Zuki, Nur Fatin Shafika; Rosli, Nur Hanisah; Mohamed, Abdul Hamid (2024)
Everlasting land is a student center or public space design that plays a crucial role in shaping the environment where university students can interact and thrive. Everlasting land was named as it encompasses principles of durability, sustainability, timeless aesthetics and contextual integration, aiming to create built environments that endure and enrich the surrounding landscape for generations to come. A growing number of schools around the United States have begun adding outdoor learning to their curriculum in hopes to improve the education of students. From lively gathering spots to serene study areas, thoughtful design elements can enhance both social connections and academic pursuits. Incorporating green spaces, comfortable seating and engaging installations fosters a sense of community and encourages collaboration among students. By creating inviting and functional public spaces, we can promote a conducive learning environment that inspires creativity, interaction and personal growth among the students.